2017
DOI: 10.1007/s00382-017-3996-z
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in modelling the climate impact of irrigation

Abstract: Irrigation-based agriculture constitutes an essential factor for food security as well as fresh water resources and has a distinct impact on regional and global climate. Many issues related to irrigation's climate impact are addressed in studies that apply a wide range of models. These involve substantial uncertainties related to differences in the model's structure and its parametrizations on the one hand and the need for simplifying assumptions for the representation of irrigation on the other hand. To addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…This suggests that the impact of irrigation on the simulated climate can differ between models despite identical irrigation implementation. These differences may originate from substantial differences in the model setup, structure and atmospheric parametrizations ( de Vrese & Hagemann, 2018). Although CESM2, GISS-E2-1-G, and NorESM2-LM implement an irrigation scheme, GISS.E2.1.G shows the strongest increase in LHF, SM, and LW net over all irrigation classes, followed by NorESM2-LM and CESM2.…”
Section: Cmip6 Simulationsmentioning
confidence: 99%
“…This suggests that the impact of irrigation on the simulated climate can differ between models despite identical irrigation implementation. These differences may originate from substantial differences in the model setup, structure and atmospheric parametrizations ( de Vrese & Hagemann, 2018). Although CESM2, GISS-E2-1-G, and NorESM2-LM implement an irrigation scheme, GISS.E2.1.G shows the strongest increase in LHF, SM, and LW net over all irrigation classes, followed by NorESM2-LM and CESM2.…”
Section: Cmip6 Simulationsmentioning
confidence: 99%
“…This discrepancy in the causes was ascribed to the fact that, in the previous version of the atmospheric model (CAM3), convection was very sensitive to the surface latent heat changes (Thiery et al, 2017). The effects of irrigation go beyond the surface cooling, as it affects the surface energy partition (e.g., Cook et al, 2015) and thus the atmospheric dynamics (Guimberteau et al, 2012;Saeed et al, 2009;Tuinenburg and de Vries, 2017;Douglas et al, 2009;Saeed et al, 2009;Lee et al, 2011), water vapor content (e.g., Boucher et al, 2004), and finally precipitation (Pielke and Zeng, 1989;Deangelis et al, 2010;Bonfils and Lobell, 2007;Puma and Cook, 2010). Some of the regional studies did not find a significant change in the cloud cover (Kueppers et al, 2007(Kueppers et al, , 2008Sorooshian et al, 2011;Qian et al, 2013), while others did (Aegerter et al, 2017;Krakauer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of irrigation on climate, especially temperature, has been assessed by various Earth system models, which have demonstrated that, despite a slight decrease in surface albedo, the net biophysical effect of irrigation is to cool surface temperature through the increase in evapotranspiration (ET) [1,2]. Modeling results are effective in presenting mechanistic understandings of the effects of irrigation on climate, but show high uncertainties in the sign, magnitude, and spatial distribution of the predicted effects, due to their heavy dependence on the model's structure and parameterization [3,4]. Observations from in-situ measurements (e.g., weather stations and field experiments) can provide local reliable evidence to verify the model results [5].…”
mentioning
confidence: 99%